Optimizing the Evacuation for Eau Claire County, Phase III - Bauer, Mark; Buell, Brian; Lafferty, Eric; Miller, Hannah (My University, 2011)
This study resulted in a mathematical model to integrate into ArcGIS, a geographical information system, so that the emergency management officers of the City of Eau Claire can obtain the optimal routes and times for an intended region to evacuate.
Color poster with text, images, maps, and charts.
Keywords: ArcGis; Evacuation of civilians--Wisconsin--Eau Claire--Planning; Evacuation of civilians--Computer programs; Geographic information systems--Computer programs; Emergency management--Wisconsin--Eau Claire--Planning; Emergency management--Computer programs; Posters